Ekspansi Pakan Alami Tepung Ubi Jalar Terhadap Intensitas Kecerahan Warna Ikan Mas Koi (Cyprinus carpio) - Wahyu, Farhanah; Andi Chadijah (Journal Galung Tropika, 2023)
Koi carp (Cyprinus carpio) is one of the attractive ornamental fish to be cultivated because it has a gorgeous color and high economic value, so koi carp is in great demand by the public. The beautiful color of koi carp is influenced by the presence of natural pigments in fish; to release that color, it is necessary to add color pigments from synthetic substances. One of the natural ingredients that contain color pigments is purple sweet potato. This study aims to determine the effect and the correct dose of adding sweet potato flour to the intensity of the color brightness of koi carp (Cyprinus carpio). This research was carried out in stages, starting with the supply of raw materials for feed and carp koi (Cyprinus carpio). Then, the use of fish color measuring instrument parameters, namely toca color, measurement of absolute growth, survival rate, feed conversion, and feed efficiency. In the next stage, the research focused on fish maintenance and using optimal feed doses against changes for 90 days. The study’s results showed that the highest change in color brightness was in treatment C (of purple sweet potato flour 15%) with a value of 6. Then, treatment A (5%), as much as 5.56, followed by treatment D (control), did not experience an increase in brightness color. Treatment B (10%) has the lowest color brightness level of 4.89. The results of these numbers are adjusted to the analysis test results (p> 0.05), which shows that the feeding of purple sweet potato flour has no significant effect on changes in the color’s brightness level, and the results of the efficiency of feed utilization.